Lipase-Catalyzed Synthesis of Medium-Long-Medium-Type of Structured Lipids from Refined Bleached Deodorized Olein - Utama, Qabul Dinanta; Sitanggang, Azis Boing; Adawiyah, Dede Robiatul; Hariyadi, Purwiyatno (Applied Food Biotechnology, 2020)
Background and objective: Medium-long-medium type of structured lipid is appropriate for the management of obesity, fat malabsorption and other metabolic disorders. No studies have been carried out on the ability of Lipozyme TL IM in two types of reaction, acidolysis and transesterification for Medium-long-medium type of structured lipids synthesis using refined bleached deodorized olein as major substrate. This study aimed to synthesize medium-long-medium type of structured lipids rich in TAG, especially with equivalent carbon number 32. Furthermore, stability of Lipozyme TL IM in acidolysis and transesterification was assessed. Materials and methods: Two methods of synthesis, transesterification (tricaprylin and refined bleached deodorized olein) and acidolysis (caprylic acid and refined bleached deodorized olein), were used to produce medium-long-medium type of structured lipid. The synthesis was catalyzed using specific sn-1,3 commercial lipase (Lipozyme TL IM). Composition of triacylglycerol substrates and products and residual activity of the enzyme were investigated. Results and conclusion: The transesterification needed approximately 4 h to achieve a maximum concentration of equivalent carbon number 32 (16.75%) this was 20 h with an equivalent carbon number 32 concentration of 16.28% for acidolysis. Lipozyme TL IM included a further stable activity for transesterification as its half-life was longer than that of acidolysis. Lipozyme TL IM was appropriate for catalyzing transesterification to produce medium-long-medium type of structured lipid rich in triacylglycerol with equivalent carbon number 32, presumably that of 1,3-dicapryoyl-2-oleoyl-sn-glycerol, compared to that for acidolysis. Conflict of interest: The authors declare no conflict of interest.